Strengthening climate and health adaptation strategies to combat cholera in Angola and beyond - Abdulrakib Abdulrahim; Valdemiro Amilton Rafael; Bashar Haruna Gulumbe; Victor Abiola Adepoju; Safayet Jamil (Journal of Interventional Epidemiology and Public Health)
As the new year begins, Angola faces a distressing surge in cholera cases [1] . On January 8, 2025, the Ministry of Health officially declared an outbreak. By February 4, a total of 2,069 suspected cases and 404 confirmed cases had been documented, with 70 deaths reported accounting for a case fatality rate of 3.4% across eight of the country’s 18 provinces [1]